Gain of chromosome region 18q21 including the MALT1 gene is associated with the activated B-cell-like gene expression subtype and increased BCL2 gene dosage and protein expression in diffuse large B-cell lymphoma - Judith Dierlamm; Eva M. Murga Penas; Stefan Bentink; Swen Wessendorf; Hilmar Berger; Michael Hummel; Wolfram Klapper; Dido Lenze; Andreas Rosenwald; Eugenia Haralambieva; German Ott; Sergio B. Cogliatti; et al. (Haematologica, 2008)
Background The aim of this study was to determine the impact of a gain of the MALT1 gene on gene expression and clinical parameters in diffuse large B-cell lymphoma.Design and Methods We analyzed 116 cases of diffuse large B-cell lymphoma by fluorescence in situ hybridization, array-based comparative genomic hybridization, and transcriptional profiling.Results A gain of 18q21 including MALT1 was detected in 44 cases (38%) and was accompanied by a gain of BCL2 in 43 cases. All cases with a 18q21/MALT1 gain showed BCL2 protein whereas 79% in the group without a 18q21/MALT1 gain did so (p